2008
DOI: 10.14411/eje.2008.031
|View full text |Cite
|
Sign up to set email alerts
|

Differences in mating strategies in two closely related small ermine moth species (Lepidoptera: Yponomeutidae)

Abstract: Abstract. The degree of polyandry in a species is linked to other life history traits such as egg maturation, life span, and male ejaculate size and quality. The study of differences in mating strategies between closely related species can provide a better understanding of the evolution of these strategies and of sperm competition. Mating patterns of two closely related species of small ermine moths (Yponomeuta) were investigated in the laboratory. The average female age at first mating was higher in Y. cagnag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 36 publications
2
8
0
Order By: Relevance
“…The hypothesis of Wiklund et al [25] implies that males of polyandrous species continue to live International Journal of Zoology after the peak of female receptivity (at least under the condition that females receptivity is synchronous, as is the case in Yponomeuta) and thus live past the moment that most females have mated once. Indeed, our results showed that in both species males live long after the peak of female receptivity: males of both species live on average more than 45 days after eclosion, but Y. cagnagellus females are receptive at 14.6 ± 1.2 (mean ± SE) days and Y. padellus females at 4.9 ± 0.6 days after eclosion [39]. We extended Wiklund's hypothesis to sex-specific lifespan differences between high and low polyandrous species and expected a larger investment in lifespan in Y. cagnagellus males; that is, we predicted a significant sex by species interaction on lifespan.…”
Section: Effect Of Degree Of Polyandry On Male Investment In Lifespanmentioning
confidence: 64%
See 3 more Smart Citations
“…The hypothesis of Wiklund et al [25] implies that males of polyandrous species continue to live International Journal of Zoology after the peak of female receptivity (at least under the condition that females receptivity is synchronous, as is the case in Yponomeuta) and thus live past the moment that most females have mated once. Indeed, our results showed that in both species males live long after the peak of female receptivity: males of both species live on average more than 45 days after eclosion, but Y. cagnagellus females are receptive at 14.6 ± 1.2 (mean ± SE) days and Y. padellus females at 4.9 ± 0.6 days after eclosion [39]. We extended Wiklund's hypothesis to sex-specific lifespan differences between high and low polyandrous species and expected a larger investment in lifespan in Y. cagnagellus males; that is, we predicted a significant sex by species interaction on lifespan.…”
Section: Effect Of Degree Of Polyandry On Male Investment In Lifespanmentioning
confidence: 64%
“…In the laboratory, they can mate up to 9 times. The average mating frequency of Y. padellus females is 2.0 ± 0.2, and a majority of females is mating only once [39]. We can therefore conclude that Y. cagnagellus females are highly polyandrous and Y. padellus females have a low degree of polyandry.…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…Females start calling for males only at the age of about 10 days (Hendrikse, 1979). The average age at first mating is 14.6 days, and females may mate with several males (Bakker et al., 2008). Individuals rarely disperse further than 100 m from their place of eclosion (Menken et al., 1992) and gene flow between populations is low (Menken et al., 1980).…”
Section: Methodsmentioning
confidence: 99%